The relationship between poverty and environmental degradation, KwaZulu-Natal - Zwane, Thamsanqa (My University, 2016)
ABSTRACT Brundtland (1987) has argued that the key to remedying environmental degradation is addressing poverty through economic growth. However, this study will argue that a weak institutional framework is the main cause of environmental degradation, suggesting a different remedy. The study will therefore dismiss economic growth as the panacea for environmental degradation. It will favour the position of the World Bank (Sham, 1993) that the most effective way to address the downward spiral within the environment-poverty relationship is to develop environmental policies that are aimed at availing employment opportunities to ‘the poor’ in rural areas. A case study in the area of Maphophoma, north of KwaZulu-Natal had been undertaken to support the proposed theoretical framework. A qualitative methodology of in-depth semistructured interviews has been used to collect data. The purpose of this study is to provide findings that will assist – specific implementation of well-researched environmental protection policies rather than blanket implementation of these policies.
MM
Keywords: Poverty -- Environmental aspects -- Environmental degradation -- Sustainable development -- South Africa.